2014
DOI: 10.1007/s10705-014-9626-9
|View full text |Cite
|
Sign up to set email alerts
|

Dinitrogen and methane gas production during the anaerobic/anoxic decomposition of animal manure

Abstract: Trace-gas emissions from animal feeding operations (AFOs) can contribute to air quality and global change gases. Previous and current estimated gas emissions from AFOs vary widely and many do not consider all forms of carbon (C) and nitrogen (N) emissions. Studies have found that as methanogenesis in the lagoons increased, conversion of ammonium (NH 4 ? ) to dinitrogen (N 2 ) also increased. The purpose of this research was to measure N 2 and CH 4 emissions from swine AFOs in three locations of the U.S. and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 24 publications
0
15
0
Order By: Relevance
“…Considering that the emissions of NH 3 had average values >200 mg m À2 h À1 of NH 3 -N, it is evident that, of those measured (NH 3 + N 2 O) the predominant N emission was in the form of NH 3 , representing on average more than 99%. As discussed above, based on the model of Harper et al (2014), we would not expect high N 2 emissions. According to Harper et al (2014), the expected N 2 would represent less than 5% of total N emissions.…”
Section: Ammonia and Nitrous Oxidementioning
confidence: 96%
See 2 more Smart Citations
“…Considering that the emissions of NH 3 had average values >200 mg m À2 h À1 of NH 3 -N, it is evident that, of those measured (NH 3 + N 2 O) the predominant N emission was in the form of NH 3 , representing on average more than 99%. As discussed above, based on the model of Harper et al (2014), we would not expect high N 2 emissions. According to Harper et al (2014), the expected N 2 would represent less than 5% of total N emissions.…”
Section: Ammonia and Nitrous Oxidementioning
confidence: 96%
“…As discussed above, based on the model of Harper et al (2014), we would not expect high N 2 emissions. According to Harper et al (2014), the expected N 2 would represent less than 5% of total N emissions. The absent or very small N 2 O fluxes from both C and P digestates in the first weeks of storage can be explained by the absence of a crust during the storage period (Berg et al, 2006;Sommer et al, 2000).…”
Section: Ammonia and Nitrous Oxidementioning
confidence: 96%
See 1 more Smart Citation
“…Although biological decomposition of animal manure in treatment lagoons results in CH 4 and CO 2 emissions (and small amounts of other gases), studies have shown significant amounts of chemical (thermodynamic) conversion of NH 4 + to dinitrogen (N 2 ) gas in lagoons in the U.S. southeastern Coastal Plains and in the Central Great Basin of Utah (Harper et al, 2000(Harper et al, , 2004(Harper et al, , 2014Weaver et al, 2012). All of these gases are emitted from the sediment layer and rise to the surface either as small gas bubbles or as an occasional large gas "breakthrough" bubble from the sediment layer where a large single emission may occur.…”
Section: Core Ideasmentioning
confidence: 99%
“…The effect of ebullition on each process needs to be understood to be able to integrate or discount biogas ebullition in NH 3 emission models. Bubble transport can be understood by taking advantage of earlier work (Harper et al, 2000(Harper et al, , 2004(Harper et al, , 2014Weaver et al, 2012) done to characterize biological decomposition gas emissions occurring in lagoons. These earlier studies determined not only the composition of the gases but also the daily ebullition rates averaged on a monthly basis.…”
mentioning
confidence: 99%